Assessment of adherence to guidelines for using progesterone to prevent recurrent preterm birth. (2nd June 2016) - Crane, Stephen S.; Naples, Robin; Grand, Cindy K.; Friebert, Sarah; McNinch, Neil L.; Kantak, Anand; Rossi, Elena; McBride, John
Abstract: Objective : To assess if women with recurrent preterm birth had been offered, received, and adhered to progesterone supplementation guidelines and to ascertain reasons for failure to follow guidelines. Methods : Charts of infants who were products of recurrent spontaneous preterm birth were reviewed at four neonatal intensive care units of Akron Children's Hospital. Mothers of identified infants were interviewed and charts abstracted to determine: if progesterone was offered; acceptance of progesterone; compliance with progesterone; and reasons why progesterone was declined. Results : One hundred twenty-eight mothers with a recurrent spontaneous preterm birth were identified and 98 consented to participate. 62.2% (61/98) of the interviewed mothers reported that they were offered progesterone. Of the women offered progesterone, 82% (50/61) accepted treatment and 18.0% (11/61) declined. One woman who accepted progesterone did not receive it. Of the women who received progesterone, 18.4% (9/49) reported compliance failure. Of the women who did not receive progesterone, 75.5% (37/49) reported that they were not offered progesterone and 89.2% (33/37) of the women not offered progesterone reported that their care providers were aware of their prior preterm delivery. Conclusions : Only 50% (49/98) of women who were candidates for progesterone received treatment. The main reason for women not receiving treatment was not being offered progesterone by their caregiver.